استخدام الاختبار الشفهي وأثره على نتائج تعلم اللغة العربية لدى طلاب الحادي عشر بالمدرسة العالية جهاي قرآن جبونبولانغ بوجور - Abrar, Muhammad (Shaut al Arabiyyah, 2024)
This paper discusses the impact of the use of the oral test on the results of Arabic learning among eighth grade high school students in Cibungbulang Bogor, and how the results of learning the Arabic language for eighth grade students in high school Goofy Punto Parana who use the oral test. This type of research is quantitative research with an experimental design approach. The population in this study was eighth grade high school students in Guppi Bonto Marennu with a total of 57 people while the sample was 30 people who were taken through random sampling technique. To obtain data on the two variables, the researchers used a test tool that the researchers conducted for each sample. The data analysis technique used is descriptive statistics and inference statistics. Based on the results of data analysis using descriptive statistics of learning outcomes without using oral tests, in this case written test is in the intermediate category. Then learning outcomes using oral tests are also in the intermediate category. The results of the meditation analysis show that the value of t is 4.4 while t is a table at the 0.05 significance level is 1.4. Thus, thitung has a greater number of ttabel and Ha is rejected, which means that there is no significant effect of the use of the oral test results of Arabic language learning for eighth grade high school students Cibungbulang Bogor.